Thief of fate (Providence Falls, 3,, 2022)
"When Liam O'Connor stole Cora McLeod from her destined soul mate, Finley Walsh, in 1844, he changed the course of history. Now Liam has been given three months to set things right, but he has failed to reunite Cora and Finn. And with time running out, things are looking worse than ever. As the three investigate a murder case together, they are caught in a devilish love triangle. Finn has always loved Cora. She has finally realized she wants Liam. And Liam knows he has no choice but to push Cora away if he has any hope of avoiding eternal damnation. The angels have made it clear-balance must be restored. As Liam tries desperately to make amends, he realizes his actions in the past have put them all in grave danger. And, once again, someone will pay the ultimate price"--

The time keeper (Hachette Books, Hyperion, Thorndike Press, Hyperion Audio, 2012)
After being punished for trying to measure God's greatest gift, Father Time returns to Earth along with a magical hourglass and a mission: a chance to redeem himself by teaching two earthly people the true meaning of time.

When: the scientific secrets of perfect timing (Random House Large Print, Riverhead Books, Penguin Audio, Books on Tape, Penguin Publishing Group, Penguin Random House Audio, 2018)
The instant New York Times Bestseller #1 Wall Street Journal Business Bestseller Instant Washington Post Bestseller "Brims with a surprising amount of insight and practical advice." —The Wall Street Journal Daniel H. Pink, the #1 bestselling author of Drive and To Sell Is Human, unlocks the scientific secrets to good timing to help you flourish at work, at school, and at home.  Everyone knows that timing is everything. But we don't know much about timing itself. Our lives are a never-ending stream of "when" decisions: when to start a business, schedule a class, get serious about a person. Yet we make those decisions based on intuition and guesswork. Timing, it's often assumed, is an art. In When: The Scientific Secrets of Perfect Timing, Pink shows that timing is really a science. Drawing on a rich trove of research from psychology, biology, and economics, Pink reveals how best to live, work, and succeed. How can we use the hidden patterns of the day to build the ideal schedule? Why do certain breaks dramatically improve student test scores? How can we turn a stumbling beginning into a fresh start? Why should we avoid going to the hospital in the afternoon? Why is singing in time with other people as good for you as exercise? And what is the ideal time to quit a job, switch careers, or get married? In When, Pink distills cutting-edge research and data on timing and synthesizes them into a fascinating, readable narrative packed with irresistible stories and practical takeaways that give readers compelling insights into how we can live richer, more engaged lives.

This time tomorrow (Random House Large Print, Findaway World, LLC, Riverhead Books, Penguin Publishing Group, Books on Tape, Penguin Random House Audio, 2022)
"What if you could take a vacation to your past, without the filter of memory? What would you give to go back in time and relive your youth, in person, with the people who shared it? On the eve of her 40th birthday, Alice's life isn't terrible. She likes her job, even if it isn't exactly the one she expected. She's happy with her apartment, her romantic status, her independence, and she adores her lifelong best friend. But something is missing. Her father, the single parent who raised her, is ailing and out of reach. How did they get here so fast? Did she take too much for granted along the way? When Alice wakes up the next morning somehow back in 1996, it isn't her 16-year-old body that is the biggest shock, or the possibility of romance with her adolescent crush, it's her dad: the vital, charming, 49-year-old version of her father with whom she is reunited. Now armed with a new perspective on her own life and his, is there anything that she should do differently this time around? What would she change, given the chance? With her celebrated humor, insight, and heart, Emma Straub cleverly turns all the traditional time travel tropes on their head and delivers a different kind of love story - about the lifelong, reverberating relationship between a parent and child"--

The time machine (Oxford world's classics, ,, 2012)
Chiltern Publishing creates the most beautiful editions of the World's finest literature. Your favorite classic titles in a way you have never seen them before; the tactile layers, fine details and beautiful colors of these remarkable covers make these titles feel extra special and will look striking on any shelf. The Time Machine offers a post-apocalyptic vision of humanity's future. A scientist builds a time machine and travels to future. He finds that humanity has devolved into two races: the childlike Eloi and the monstrous Morlocks. His machine disappears, so he explores but realizes that the future world is nothing like what he had envisaged or hoped for. After narrowly escaping from the Morlocks, the Time Traveller undertakes another journey even further into the future where he finds the earth growing bitterly cold as the heat and energy of the sun diminished. Horrified, he returns to the present, but soon departs again on his final journey

Dinosaurs before dark (Magic tree house. Original series, 1, 1, 1995)
Eight-year-old Jack and his younger sister Annie find a magic tree house, which whisks them back to an ancient time zone where they see live dinosaurs.
Into the woods , The monster , Where is here? , Henry , Gold in the grass , Dinosaur valley , Ready, set, go! , A giant shadow , The amazing ride , Home before dark.

An impossible promise (Providence Falls, 2, 1, 2021)
"Liam O'Connor has one purpose in this life, to push the woman he loves into the arms of another man. The Irish rogue unknowingly changed the course of destiny when he fell in love with Cora McLeod over a century ago. Their passion was intense, brief and tragic. And the angels have been trying to restore the balance of fate ever since." - Provided by publisher.

The rise and fall of D.O.D.O (D.O.D.O, 1, 1, 2017)
"When Melisande Stokes, an expert in linguistics and languages, accidentally meets military intelligence operator Tristan Lyons in a hallway at Harvard University, it is the beginning of a chain of events that will alter their lives and human history itself. The young man from a shadowy government entity approaches Mel, a low-level faculty member, with an incredible offer. The only condition: she must sign a nondisclosure agreement in return for the rather large sum of money. Tristan needs Mel to translate some very old documents, which, if authentic, are earth-shattering. They prove that magic actually existed and was practiced for centuries. But the arrival of the scientific revolution and the Age of Enlightenment weakened its power and endangered its practitioners. Magic stopped working altogether in 1851, at the time of the Great Exhibition at London's Crystal Palace--the world's fair celebrating the rise of industrial technology and commerce. Something about the modern world "jams" the "frequencies" used by magic, and it's up to Tristan to find out why. And so the Department of Diachronic Operations, D.O.D.O., gets cracking on its real mission: to develop a device that can bring magic back, and send Diachronic Operatives back in time to keep it alive . . . and meddle with a little history at the same time."--

The time traders (Time traders, 1, 1, 2017)
The Time Traders Andre Norton - The first novel in the classic series, in which wars are no longer fought on land, in the air, or on the sea-but throughout time and space itself . . . The never-ending tension between Russia and the United States has been escalated by a stunning new variable: time travel. While the Americans can roughly utilize the technology, the Russians have learned the secret of space travel-and that makes the US vulnerable. What they need is someone expendable to send through time to obtain the same secret. Ross Murdock doesn't consider himself expendable. He's just a smart guy who made some bad choices that led him to a life of crime. But when he's given a choice between medical "rehabilitation" and joining the mysterious Operation Retrograde, he decides to go along with the military option and hope for a chance to get away. And he is going to get away-farther away than he ever imagined . . . The Time Traders is the first book in the Time Traders Series, but you may enjoy reading the series in any order.

Chance of a lifetime (Providence Falls, 1, 1, 2020)
"In one century she loved him madly, and in another she wants nothing to do with him. In 1844 Ireland, Liam O’Connor, a rogue and a thief, fell madly in love with a squire’s daughter and unwittingly altered the future. Shy and naive Cora McLeod thought Liam was the answer to her prayers. But the angels disagreed and they’ve been waiting for the right moment in time to step in. Now Liam finds himself reunited with his beloved Cora in Providence Falls, North Carolina. The angels have given Liam a task. He must make sure Cora falls in love with another man—the one she was supposed to marry before Liam interfered. But this Cora is very different from the innocent girl who fell for Liam in the past. She’s a cop and has a confidence and independence he wasn’t expecting. She doesn’t remember Liam or their past lives, nor is she impressed with his attempts to guide her in any way. Liam wants Cora for himself, but with his soul hanging in the balance, he must choose between a stolen moment in time or an eternity of damnation." --book jacket

Wrong place wrong time: a novel (Reese's book club, 2022,, 2022)
"Late October. After midnight. You’re waiting up for your seventeen-year-old son. He’s late. As you watch from the window, he emerges, and you realize he isn’t alone: he’s walking toward a man, and he’s armed. You can’t believe it when you see him do it: your funny, happy teenage son, he kills a stranger, right there on the street outside your house. You don’t know who. You don’t know why. You only know your son is now in custody. His future shattered. That night you fall asleep in despair. All is lost. Until you wake . . . and it is yesterday. And then you wake again . . . and it is the day before yesterday. Every morning you wake up a day earlier, another day before the murder. With another chance to stop it. Somewhere in the past lies an answer. The trigger for this crime—and you don’t have a choice but to find it . . . " --publisher's website.

Hazards of time travel (Harper Collins Publishers, Ecco, an imprint of HarperCollinsPublishers, HarperCollins, HarperAudio, Findaway World, LLC, Harper Audio, 2018)
A recklessly idealistic girl dares to test the perimeters of her tightly controlled (future) world and is punished by being sent back in time to a region of North America - "Wainscotia, Wisconsin" - that existed eighty years before. Cast adrift in time in this idyllic Midwestern town she is set upon a course of "rehabilitation" - but cannot resist falling in love with a fellow exile and questioning the constrains of the Wainscotia world with results that are both devastating and liberating.

Hurricane heroes in Texas (Magic tree house. Original series, 30, 1, 2018)
When Jack and Annie travel back in time to Galveston, Texas, on September 8, 1900, they find themselves facing a horrific storm that resulted in the worst natural disaster in US history.

Oona out of order (Thorndike Press large print core, ,, 2020)
"Time Traveler's Wife meets Eternal Sunshine of the Spotless Mind in a wondrous novel exploring the burdens of time, the endurance of love, and the timelessness of family. Just because life might be out of order, doesn't mean it's broken. It's new years eve 1982, and Oona Lockhart has her whole life before her. At the stroke of midnight she will turn nineteen, and the year ahead promises to be one of consequence. Should she go to London to study economics, or follow her heart and remain at home in Brooklyn to be with her boyfriend? As the countdown to the new year begins, Oona feels lightheaded, woozy, and it's not from the champagne. At the stroke of midnight Oona is torn from her life and everyone she loves, finding herself in her 51 year old body thirty-three years into the future. Greeted by a friendly stranger in a beautiful house she's told is her own, Oona learns that will with each passing year she will leap to another age at random. Still a young woman on the inside, but ever changing on the outside, who will she be next year? Philanthropist? Club kid? World traveler? Wife to a man she's never met? Hopping through decades, and a lifetime Oona Out of Order is a surprising, magical novel that explores the power of love, the bonds of family, and the wonders of life"--

The Halloween tree (Recorded Books, Inc., Blackstone Audio, Knopf, Blackstone Publishing, Gauntlet Publications, 2008)
A group of children and a "spirit" go back through time to discover the beginnings of Halloween.

Astrophysics for people in a hurry (Thorndike Press large print lifestyles, ,, 2017)
"The essential universe, from our most celebrated and beloved astrophysicist. What is the nature of space and time? How do we fit within the universe? How does the universe fit within us? There's no better guide through these mind-expanding questions than acclaimed astrophysicist and best-selling author Neil deGrasse Tyson. But today, few of us have time to contemplate the cosmos. So Tyson brings the universe down to Earth succinctly and clearly, with sparkling wit, in tasty chapters consumable anytime and anywhere in your busy day. While you wait for your morning coffee to brew, for the bus, the train, or a plane to arrive, Astrophysics for People in a Hurry will reveal just what you need to be fluent and ready for the next cosmic headlines: from the Big Bang to black holes, from quarks to quantum mechanics, and from the search for planets to the search for life in the universe"--
The greatest story ever told , On Earth as in the heavens , Let there be light , Between the galaxies , Dark matter , Dark energy , The cosmos on the table , On being round , Invisible light , Between the planets , Exoplanet earth , Reflections on the cosmic perspective.

The order of time (Riverhead Books, Penguin Audio, Books on Tape, Penguin Publishing Group, Center Point Large Print, 2018)
"Why do we remember the past and not the future? What does it mean for time to "flow"? Do we exist in time or does time exist in us? In lyric, accessible prose, Carlo Rovelli invites us to consider questions about the nature of time that continue to puzzle physicists and philosophers alike"--
Preface : perhaps time is the greatest remaining mystery , The crumbling of time , Loss of unity , Loss of direction , The end of the present , Loss of independence , Quanta of time , The world without time , The world is made of events, not things , The inadequacy of grammar , Dynamics as relation , The sources of time , Time is ignorance , Perspective , What emerges from a particularity , The scent of the madeleine , The source of time.

The invisible hour: a novel (Simon & Schuster Audio, Atria Books, Center Point Large Print, 2023)
"One brilliant June day when Mia Jacob can no longer see a way to survive, the power of words saves her. The Scarlet Letter was written almost two hundred years earlier, but it seems to tell the story of Mia's mother, Ivy, and their life inside the Community -- an oppressive cult in western Massachusetts where contact with the outside world is forbidden, and books are considered evil. But how could this be? How could Nathaniel Hawthorne have so perfectly captured the pain and loss that Mia carries inside her? Through a journey of heartbreak, love, and time, Mia must abandon the rules she was raised with at the Community. As she does, she realizes that reading can transport you to other worlds or bring them to you, and that readers and writers affect one another in mysterious ways. She learns that time is more fluid than she can imagine, and that love is stronger than any chains that bind you. As a girl Mia fell in love with a book. Now as a young woman she falls in love with a brilliant writer as she makes her way back in time. But what if Nathaniel Hawthorne never wrote The Scarlet Letter? And what if Mia Jacob never found it on the day she planned to die? Nathaniel Hawthorne wrote: A single dream is more powerful than a thousand realities. This is the story of one woman's dream. For a little while it came true."--

Opposite of always (Harper Collins Publishers, Katherine Tegen Books, HarperCollins, Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2019)
After falling for Kate, her unexpected death sends Jack back in time to the moment they first met, but he soon learns that his actions have consequences when someone else close to him dies.

Cassandra in reverse (Reese's book club, ,, 2023)
"Cassandra Penelope Dankworth is a creature of habit. She likes what she likes (museums, jumpsuits, her boyfriend, Will) and strongly dislikes what she doesn't (mess, change, her boss drinking out of her mug). Her life runs in a pleasing, predictable order...until now. She's just been dumped. She's just been fired. Her local café has run out of banana muffins. Then, something truly unexpected happens: Cassie discovers she can go back and change the past. Now, Cassie should be able to find a way to fix the life she accidentally obliterated. And with time on her side, how hard can it be?" --